Swap transactions - Central Bank of Nigeria, Research Department (Abuja, Nigeria Central Bank of Nigeria, 2016)
Attempts to discuss the concept of swap transactions and their types; its pricing and valuation and the risks associated with them.
Includes bibliographical references.
oif 01/06/17
Ref.
Keywords: Swaps; Financial derivatives